Legal Certainty of Patients’ Right to Autonomy Protection in High-Risk Health Services - Anggra Yudha Ramadianto; Neni Sri Imaniyati (West Science Law and Human Rights, 2024)
The relationship between medical personnel and patients in health services should be viewed as a legal relationship between humans who have equal rights. There are two basic human rights in health services, the right to autonomy and the right to information. The results of the study indicate that the protection of patients' autonomy rights is one of the principles in biomedical ethics used as the moral basis for the provision of health services. The form of protection of patients' autonomy rights in health services is realized through regulations related to Informed Consent in Law Number 17 of 2023 Concerning Health and Minister of Health Regulation Number 290 of 2008 Concerning Consent to Medical Actions. Meanwhile, regulations related to the protection of patients' autonomy rights for high-risk health care actions have not met legal certainty because the health care actions are not classified as high-risk.